State Plan Proposals Eight Five Year Plan (1990-95) and Annual Plan (1991-92) Volume-I Government of West Bengal - Planning Commission (Planning Commission, 1990)
The single most important issue confronting the nation today is the problem of widespread and increasing unemployment. We have to accept at the national level the challenge of making an effective dent on this problem. We have to adopt, therefore, a correct policy-package in this regard. While seeking this policy on employment, it is important to enquire, at the outset, as to why our economy has failed in the past to generate adequate employment. Unless we can locate the root cause, guest for a solution may again on misdirected.
Government of West Bengal, Development and Planning Department